Projeto minerva: rádio educativo no contexto da ditadura militar - Pinheiro, Giovani Gonçalves (2016)
The Minerva Project was a distance learning project of the Brazilian Ministry of Education (MEC) which used radio as its main medium. It began in the second half of 1970, remaining until the early 1990s and it was intended to offer supplementary training for adults. The program, half an hour in length, was aired on a mandatory basis, from Monday to Friday on a national radio chain. The program was complemented by a magazine sent by the post office to the radiopostos - places where students, along with a monitor, had access to the radio receiver. The project was implemented by the Brazilian government during the military regime; however, during this research, a public collection of documents of Paraná State was discovered, which suggested a "Communist infiltration” in the radio program produced by MEC. Thus, the interest became to understand the Minerva Project, its origins, organization and forms of educational activities, seeking to capture the political-ideological struggle undertaken in that context. The primary sources used in the analysis (the State of Paraná's public collection documents) came from literature by Pinto (2013; 2014), Ferraretto (2010; 2014; 2016), Aggarwal (2007). In addition, an interview with one of the coordinators of the Project, Professor Marlene Blois (2015), contributed to the analysis. In conclusion, due to the censorship of the military regime in place at the time, and the content of the radio program being pre-recorded, there was no possibility of an ideological transmission.